THE LESSON LIFE OF SANTIAGO AS MAIN CHARACTER IN COELHO’S THE ALCHEMIST - Irmawati, Irmawati; Arafah, Burhanuddin; Abbas, Herawaty (JURNAL ILMU BUDAYA, 2020)
This paper  aims to elaborate the  lessons life from Santiago as the main character in the novel The Alchemist, especially in the current milineal  era where the presence of technology is very rapid. This condition requires young people to keep learning human values that technology does not thought it. Literary works as one of the ideas that produce cultural works reflect human values through characters in novel stories. This journal focuses on the study of the main characters using a dynamic literary approach. In analyzing the text data, the  researchers used the qualitative descriptive method. The results of this study teach the reader several things, namely; First, the life is a struggle that must be resolved wholeheartedly. Second, everyone must learn from anything and anyone including animals because whatever happens in the universe is actually a teacher. Then the human  must dare to fight for and be responsible for life by accepting all the consequences. Finally, each problem of life must be faced patiently.